2017
DOI: 10.1007/s11274-017-2376-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the underlying mechanism of Saccharomyces cerevisiae in response to ethanol stress employing RNA-seq analysis

Abstract: Saccharomyces cerevisiae has been widely used for wine fermentation and bio-fuels production. A S. cerevisiae strain Sc131 isolated from tropical fruit shows good fermentation properties and ethanol tolerance, exhibiting significant potential in Chinese bayberry wine fermentation. In this study, RNA-sequence and RT-qPCR was used to investigate the transcriptome profile of Sc131 in response to ethanol stress. Scanning Electron Microscopy were carried out to observe surface morphology of yeast cells. Totally, 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…5D ). According to Li et al ( 63 ), HSP104 (a member of the protein quality control complex), together with the ubiquitin-proteasome proteolytic pathway, is required for protein disaggregation and degradation of misfolded proteins under ethanol stress, among others ( 63 ). Additionally, protein disaggregase Hsp104 is mediated, propagated, and transmitted efficiently to newly formed buds ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…5D ). According to Li et al ( 63 ), HSP104 (a member of the protein quality control complex), together with the ubiquitin-proteasome proteolytic pathway, is required for protein disaggregation and degradation of misfolded proteins under ethanol stress, among others ( 63 ). Additionally, protein disaggregase Hsp104 is mediated, propagated, and transmitted efficiently to newly formed buds ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Li et al (23) has shown that upregulation of the genes involved in thiamine and thiamine pirophosphate (TPP) biosynthetic processes are important against ethanol stress in S. cerevisiae. In the present study, after the effective thiamine concentration was determined by using H 2 O 2 -induced oxidative stress (Figure 1b), we examined the effect of 1.5 ”M thiamine on cell viability under osmotic and heat stresses, which were triggered with sorbitol and high-temperature, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentration was measured by QubitÂź RNA Assay Kit in QubitÂź 2.0. And RNA integrity and purity were evaluated using the RNA Nano 6000 Assay Kit and the NanoPhotometerÂź spectrophotometer (Implen) [20]. The construction of the libraries and the RNA-Seq were performed by LC-Bio Technology Co., Ltd.…”
Section: Evaluation Of Acid and Osmotic Cross-resistancementioning
confidence: 99%